Stroke services in MENA: What is there and what is needed. - Hany Aref; Nevine El Nahas; Suhail Abdulla Alrukn; Maria Khan; Selma Kesraoui; Firas Alnidawi; Elyar Sadeghi Hokmabadi; Mehdi Farhoudi; Muataz Fairooz; Waleed Batayha; Athari Salmeen; Husen Abdulrahman; et al. (PLoS ONE)
Objectives Stroke represents a health care challenge to most parts of the world including the Middle East and North Africa (MENA) region. The MENA represents 6% of the world population with an age-standardized stroke rate of 87.7 (78.2-97.6) per 100,000 population. This number is subject to increase given that the cause of morbidity has recently shifted from infectious diseases to non-communicable diseases. Thus, in the coming years, treatment of stroke will pose a major burden on MENA countries which mostly lie in the low to middle income economies. Accordingly, we need to study the state of MENA stroke services in order to recognize and further inform policy makers about any gaps that need to be bridged in this domain. Methods and results Stroke specialists representing 16 countries filled an online survey that included: screening for risk factors, acute management, diagnostics, medications, post-discharge services, and stroke registries. Results showed that 11 countries screen for risk factors, 16 have neuroimaging studies, 15 provide intravenous thrombolysis (IVT), 13 mechanical thrombectomy (MT) while medications for secondary prevention are available in all countries. However, stroke units are not equally available and even absent in 4 countries, and despite the availability of IVT yet, the rate of administration is still low in 6 countries (<5%), and ranges from 5-20% in 7 countries. Stroke registries and training still need to be implemented in most countries. Conclusion Although imaging, revascularization therapies and medications for secondary prevention are available in most MENA countries, yet the rate of revascularization is low, so is the number of stroke units insufficient in some countries. Additionally, registries and structured training are still defective. Further field studies are required for more accurate determination of the status of stroke services in the MENA region.